Late diagnosis of HIV: An updated consensus definition. Issue 11 (8th November 2022) - Croxford, Sara; Stengaard, Annemarie Rinder; Brännström, Johanna; Combs, Lauren; Dedes, Nikos; Girardi, Enrico; Grabar, Sophie; Kirk, Ole; Kuchukhidze, Giorgi; Lazarus, Jeffrey V.; Noori, Teymur; Pharris, Anastasia; et al.
Abstract: Introduction: In recent years, HIV testing frequency has increased, resulting in more people being diagnosed during seroconversion with a temporarily low CD4 count. Using the current consensus definition of late HIV presentation ('presenting for care with a CD4 count < 350 cells/μL or an AIDS‐defining event, regardless of CD4 count') these individuals would be incorrectly assigned as being diagnosed late. Methods: In spring 2022, a European expert group convened to revise the current late HIV presentation consensus definition. A survey on data availability to apply this revised definition was sent to nominated European focal points responsible for HIV surveillance ( n = 53). Results: Experts agreed that the updated definition should refer to late HIV diagnosis rather than presentation and include the following addition: People with evidence of recent infection should be reclassified as 'not late', with evidence of recent infection considered hierarchically. The individual must have: (i) laboratory evidence of recent infection; (ii) a last negative HIV test within 12 months of diagnosis; or (iii) clinical evidence of acute infection. People with evidence of being previously diagnosed abroad should be excluded. A total of 18 countries responded to the survey; 83% reported capturing CD4 count and/or AIDS at diagnosis through national surveillance, 67% captured last negative test and/or previous HIV diagnosis, 61% captured seroconversion illness at diagnosis and 28% captured incident antibody results. Conclusions: Accurate data on late diagnosis are important to describe the effects of testing programmes. Reclassification of individuals with recent infection will help to better identify populations most at risk of poor HIV outcomes and areas for intervention.